THE ROLE OF THE EXTERNAL AUDITOR IN REDUCING THE RISKS OF ELECTRONIC DISCLOSURE OF FINANCIAL REPORTS IN IRAQI COMPANIES / AN APPLIED STUDY IN A SAMPLE OF AUDITING COMPANIES IN BAGHDAD - Adheem naeem bachi; Karrar mohammed AL-Shafeay; hayder Hussein jawad; NaserMohsin Jebur (Scholar Express Journals, 2023)
The electronic disclosure of financial reports and statements is a new challenge for the accounting and auditing professions, so the electronic disclosure of financial reports may be accompanied by many problems, including the credibility of these reports, and the confidence of users in what they contain and the accompanying disclosures, so the study addressed the role of the auditor in limiting or minimizing The risks of electronic disclosure of financial reports and by providing the auditor with many confirmatory services that will contribute to reducing the risks of electronic disclosure of electronically published data.Among the most important of these services is what is known as continuous auditing and web trust assurance services, and therefore the role of the auditor is no longer limited to checking reports and financial statements and expressing an opinion but rather provides services represented in confirming whether the information is guaranteed and its quality, in addition to being responsible for providing it to a new category other than contributors.
Keywords: external auditor; disclosure; financial reports and statements